Between the lines. - Yuniza Djohan Khoo. (2012)
“Between The Lines” is a multi-sensory interactive installation where the concept of an impossibility being made possible is tested. It is an exploration of space where two realms are created – the physical realm and the imagined realm. In this project, a video of you is projected on a thick screen of mist, creating a live three- dimensional version of you. In this installation, the viewer steps up to a structure that frames a horizontal panorama of elusive mist. A video camera simultaneously captures viewers in front of it and projects them onto the mist from the top via a projector. This whole process creates a hazy three-dimensional effect of the image captured. How can one be at two places at once? With the availability of media, this paradoxal situation is simulated.